Optimasi Penggunaan Input Produksi pada Usahatani Kentang di Dataran Tinggi Dieng, Jawa Tengah - Dewi Sahara; Munir Eti Wulanjari; Joko Triastono (Institut Pertanian Bogor, 2023)
Potato is one of the horticultural crops with high economic value and potential as an export commodity. The productivity of potatoes in Central Java tends to decrease, and it is suspected that the use of production inputs is not optimal. This study aims to evaluate the performance of the use of production inputs, the factors that influence potato production, and the optimization of the use of production inputs in potato farming in the Dieng Plateau. The research was conducted from October to December 2021 in Sumberejo Village, Batur Subdistrict, Banjarnegara District, which has an altitude of + 1700 meters above sea level. This research used a survey method on 30 potato farmers. The data obtained were analyzed descriptively, and analyzed the factors that influence production using multiple linear regression, followed by an optimization test on the use of production inputs. The results showed that the use of production inputs among farmers still varied and had not followed the results of soil analysis. Seed, manure, and labor are production inputs that have a significant positive effect on potato production. To get maximum production, farmers need to add seeds, NPK fertilizer, and manure according to recommendations, while the use of labor needs to be reduced to achieve optimal yields. Keywords: highlands, inputs, increased production, potato, production